ANALISIS KEPUASAN PELANGGAN TERHADAP FASILITAS PELAYANAN PUBLIK PADA PENGGUNA TRANS JAKARTA - Agus Dharmanto; Novita Wahyu Setyawati; Dewi Sri Woelandari PG (Sekolah Tinggi Pariwisata Mataram, 2022)
Public transportation activities are developing so rapidly, so that every public transportation business, one of which is the Trans Jakarta public transportation, is renovating and improving services from all aspects. Where these aspects start from the renovation of the bus stop, comfort, service and security in Trans Jakarta as well as the accuracy of arrival and departure schedules. The forms of service improvement as described above make Trans Jakarta service users feel satisfied. In marketing strategy, to increase sales, an important factor that needs to be considered is the level of customer satisfaction. Monitoring customer satisfaction that is carried out properly is a material for conducting accountable evaluations for decision making related to improving Trans Jakarta services, fulfilling service processes needed by customers, and improving service processes to customers. The purpose of this study is to see the extent to which public service facilities are influenced by the quality of service for trans Jakarta users. In addition, to see how much public service facilities are affected by the quality of service for Trans Jakarta users. The method used in this study is a quantitative method using SPSS 24.0 software